2019
DOI: 10.1002/mgg3.1020
|View full text |Cite
|
Sign up to set email alerts
|

Association of MTHFR C677T polymorphism and type 2 diabetes mellitus (T2DM) susceptibility

Abstract: IntroductionMethylenetetrahydrofolate reductase (MTHFR) is essential in mediating folate metabolism, and thus plays an important role in diabetes and diabetic complications. MTHFR C677T (rs1801133 C>T) polymorphism has been proposed to be linked with type 2 diabetes mellitus (T2DM) susceptibility. However, the conclusions are inconsistent. Therefore, we rechecked their linkage aiming to obtain a more reliable estimation by performing an updated meta‐analysis.MethodsWe searched electronic databases PubMed, EMBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 52 publications
0
15
0
1
Order By: Relevance
“…MTHFR enzyme have a key role in homocysteine and folate metabolism, it is shown that homozygous (TT) and heterozygous (CT) genotypes reduce the enzyme activity by 70% and 35%, respectively, compared to the wild type CC genotype and thus may associated with increased plasma homocysteine levels and with T2DM or its complications. 16,17 The frequency of 677TT genotype is highly variable among the diabetic population. Our study showed that the overall frequency of 677TT genotype was 9.1% in all diabetic subjects, which is lower than that in Egypt (32.5%) 25 and Israel (18%), 26 but it is in agreement with some countries in the region such as Iran 7% 27 and Turkey 7%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MTHFR enzyme have a key role in homocysteine and folate metabolism, it is shown that homozygous (TT) and heterozygous (CT) genotypes reduce the enzyme activity by 70% and 35%, respectively, compared to the wild type CC genotype and thus may associated with increased plasma homocysteine levels and with T2DM or its complications. 16,17 The frequency of 677TT genotype is highly variable among the diabetic population. Our study showed that the overall frequency of 677TT genotype was 9.1% in all diabetic subjects, which is lower than that in Egypt (32.5%) 25 and Israel (18%), 26 but it is in agreement with some countries in the region such as Iran 7% 27 and Turkey 7%.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, a recently emerged meta-analysis indicated that MTHFR C677T polymorphism was significantly linked to T2DM, especially in Asian populations. 17 Type 2 diabetes mellitus is considered a secondary cause of dyslipidemia and untreated diabetic patients can suffer from poor management response which leads to hyperlipidemia-related complications, the most serious are cardiovascular ones. 18 People with T2DM may have different types of dyslipidemias.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the American College of Medical Genetics and Genomics guidelines recommended in 2013 against routine MTHFR genetic testing in cardiovascular diseases [36], a study conducted by Biselli et al has suggested a strong association between coronary artery disease incidence and MTHFR A1298C mutation [37]. Meng et al [38] and Zhu et al [39] already tried to analyze the association between this mutation in the MTHFR gene and T2DM, but the concomitant presence of cardioembolic ischemic stroke was not included in their analysis. Another study by Hermans MP et al [40] demonstrated on a relatively small cohort (165 patients) the link between C677T polymorphism (both homozygous and heterozygous) and the risk for ischemic stroke in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of either variant leads to amino acid base pair changes that ultimately reduce enzyme activity, and variant carrier status has been linked to risk of metabolic syndrome in patients treated with antipsychotics (11,(16)(17)(18)(19). Variants within the MTHFR gene have also been studied in patients without serious mental illness, and associations with variant carrier status and inflammation, adverse metabolic outcomes, and cardiovascular events have been inconsistent and in some studies dependent on population, age, or folate serum levels (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%